Ligand–Metal Cooperating PC(sp3)P Pincer Complexes as Catalysts in Olefin Hydroformylation. Issue 50 (7th November 2013) - Musa, Sanaa; Filippov, Oleg A.; Belkova, Natalia V.; Shubina, Elena S.; Silantyev, Gleb A.; Ackermann, Lutz; Gelman, Dmitri
<x xml:space="preserve">Abstract</x> Ligand–metal cooperation: A new ligand–metal cooperating catalyst for the hydroformylation of olefins is described (see scheme). The mechanism of the H2 activation and CH bond formation of the catalyst involves an intramolecular cooperation between the structurally remote functionality and the metal center and proceeds without change of the oxidation state of the metal.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>